2006
DOI: 10.2174/157340006775101472
|View full text |Cite
|
Sign up to set email alerts
|

Issues in the Psychiatric Screening of Cancer Patients

Abstract: The experience of cancer represents a unique challenge to both the physical and psychological health of the individual. High levels of distress are common in cancer patients irrespective of the type of pathology. However, the physiological aspects of the disease process may be a source of confound in the psychiatric screening process, thereby reducing the accuracy of case identification. The current review examines the salient factors which should be considered by clinicians when screening for clinically signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…The relationship between pain and sleep has often been assumed to be reciprocal -pain can lead to disturbed sleep, and vice versa (Smith & Haythornthwaite 2004). A previous review also indicated that the psychological burden of the diagnosis and treatment of cancer can reach clinically significant levels (Martin & Cheng 2006). In a study of patients with advanced cancer receiving palliative care, Delgado-Guay et al (2011) revealed that patients with sleep disturbance were more likely to report pain (P = 0.0132), depression (P = 0.019), anxiety (P = 0.01) and a poorer sense of well-being (P = 0.035) compared with patients who did not experience sleep disturbance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between pain and sleep has often been assumed to be reciprocal -pain can lead to disturbed sleep, and vice versa (Smith & Haythornthwaite 2004). A previous review also indicated that the psychological burden of the diagnosis and treatment of cancer can reach clinically significant levels (Martin & Cheng 2006). In a study of patients with advanced cancer receiving palliative care, Delgado-Guay et al (2011) revealed that patients with sleep disturbance were more likely to report pain (P = 0.0132), depression (P = 0.019), anxiety (P = 0.01) and a poorer sense of well-being (P = 0.035) compared with patients who did not experience sleep disturbance.…”
Section: Discussionmentioning
confidence: 99%
“…The literature indicates that mood disturbance often increase during the treatment period (Glajchen 1999;Palesh et al 2010) and should not be neglected. A previous review also indicated that the psychological burden of the diagnosis and treatment of cancer can reach clinically significant levels (Martin & Cheng 2006). Nevertheless, it seems possible that mood disturbance was not merely additive in its influence on the patients' functional status and QoL.…”
Section: Discussionmentioning
confidence: 99%
“…The HADS depression subscale has exhibited promising psychometric properties with older cancer patients (Martin and Cheng, 2006), but may have less face validity with homebound elders because it does not contain items assessing suicide ideation or loneliness which are especially salient to homebound older adult populations (Mitty and Flores, 2008; Barg et al ., 2006). The HADS anxiety scale appears valuable to measure severity of anxiety symptoms but exhibits poor sensitivity and specificity for screening in older medical patients (Davies et al ., 1993, Johnson et al ., 1995).…”
mentioning
confidence: 99%